A half-wave electromagnetic energy-harvesting tie towards safe and intelligent rail transportation. (1st May 2022) - Pan, Yu; Zuo, Lei; Ahmadian, Mehdi
Highlights: An innovative energy harvesting tie is designed to improve railroad safety. A novel ball screw based mechanical motion half-wave rectifier is proposed. A nonlinear model is developed to understand dynamics and predict performance. Test results show 16.1–44.5 W average power with field-recorded displacements. Abstract: This paper presents the design, modeling, and experimental testing of a novel railroad energy harvesting tie for improving rail safety and connectivity and bringing intelligence to the railroad. The system is intended for applications that require trackside power in remote locations and tunnels, where electrical power for wayside safety equipment, wireless communication systems, and health monitoring systems is needed but difficult to supply. Designed to have nearly the same dimensions as a conventional railroad tie, the proposed energy harvesting tie can be installed in the same manner as a standard tie on a track. Two rotary electromagnetic energy harvesters are embedded and shielded inside the energy harvesting tie, and the integrated system is capable of generating electricity from the vertical track movement due to passing wheels, in a robust configuration that is suitable for the railroad environment. The integration of the harvesters into a composite tie that has the same appearance of other ties makes less variable to theft and vandalism. A novel ball-screw type mechanical motion half-wave rectification mechanism is adopted in the proposed design to harvest the kinetic energy of the track during its downward motion and rebound upward without any resistance from the harvesters. A simulation study is performed to better understand the system and predict the performance, based on a nonlinear model. Experiments are subsequently carried out in a load frame on a half-tie prototype with both sinusoidal and field-recorded track displacements to measure the amount of power that can be harvested under ideal conditions and actual field conditions. The test results, which agree well with the simulations, indicate a maximum of 78.1% mechanical efficiency is achieved under harmonic excitations. Field-recorded tie displacements yield 16.1–44.5 W of average power depending on the electrical loads, sufficient for powering sensor suite and trackside electronics that could improve track monitoring and safety.